Assessment of pragmatic impairment in right hemisphere damage. (August 2016) - Parola, Alberto; Gabbatore, Ilaria; Bosco, Francesca M.; Bara, Bruno G.; Cossa, Federico M.; Gindri, Patrizia; Sacco, Katiuscia
Abstract: Aim of the present study is to provide a multifocal assessment of pragmatic abilities in patients with right hemisphere damage (RHD). Pragmatics refers to the ability to use language and non-verbal expressive means (e.g., gestures) to convey meaning in a given context, and it also involves the appropriate use of connotative elements such as rhythm and prosody. Patients with RHD frequently report a wide range of pragmatic disorders: despite the heterogeneity of their clinical profiles, these difficulties can seriously undermine their ability to effectively communicate in everyday situations. We analysed the performance of 17 patients with RHD and 17 healthy controls using the Assessment Battery for Communication, a clinical tool for assessing a wide range of pragmatic phenomena - both in comprehension and production - and considering different expressive means. The results suggest patients have difficulties both in comprehending and producing pragmatic phenomena of differing complexity; in particular, patients seem to be significantly impaired when dealing with non-verbal modality, i.e., gestures and facial expressions. Moreover a hierarchical cluster analysis revealed the presence of a number of clusters corresponding to different outcomes of pragmatic performance, in line with the heterogeneity of communicative profiles following RHD frequently reported in the literature. Highlights: Assessment of communicative-pragmatic abilities in RHD patients. Lack of comprehensive assessment tools. Most critical impairments concern the management of non-verbal modality. Heterogeneity of the communicative profile following RHD.